Atypical presentation of psoriasis on the breast of an elderly woman: A case report - Susuana Adjei; Mohamad R Taha; Anisha B Patel; Stephen K Tyring (SAGE Open Medical Case Reports)
Psoriasis is a chronic, inflammatory skin disease that affects over 60 million adults and children globally. It is classically characterized by pink plaques covered with silver scales on the extensor surfaces, trunk, or scalp. In this report, we describe the case of a woman in her late 60s with psoriasis presenting as a painful plaque on her left breast. This case highlights the importance of considering psoriasis as a differential diagnosis in patients with unilateral breast plaques, even in the absence of typical psoriasis scaling elsewhere on the body.